Pengaruh Partisipasi Penyusunan Anggaran, Kejelasan Sasaran Anggaran, Profesionalisme Terhadap Kinerja Aparatur Pemerintah Daerah Kota Bukittinggi - Rahmiwati Rahmiwati; Ria Ariany (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2023)
This study intends to: (1) describe how local government officials' performance in the City of Bukittinggi is affected by their involvement in budgeting. (2) explains how the performance of local government representatives in Bukittinggi City is impacted by the clarity of budget targets. (3) Describe how professionalism affects how local government representatives in the City of Bukittinggi perform. The Regional Apparatus Organization (OPD) in the Regional Government of the City of Bukittinggi is the subject of this study. The 409-person population of the 30 OPD where the questionnaire was distributed was the source of the primary data. The sample in this study was the team responsible for creating the budget, which included the 72-person Regional Government of Bukittinggi City's Head of Service, Head of Planning Sub-division, and Technical Implementation Officers for Activities. utilizing a quantitative strategy and PLS SEM model data analysis. The findings of this study suggest that: (1) Local government officials' performance in the City of Bukittinggi is positively and significantly impacted by their involvement in budgeting. (2) The performance of the local government apparatus of the City of Bukittinggi is positively and significantly impacted by the clarity of the budget targets; (3) The performance of the regional government apparatus of the City of Bukittinggi is negatively and insignificantly impacted by professionalism. ABSTRAK Penelitian ini bertujuan untuk (1) menguraikan pengaruh partisipasi penyusunan anggaran terhadap kinerja aparatur pemerintah daerah Kota Bukittinggi. (2) menguraikan pengaruh kejelasan sasaran anggaran terhadap kinerja aparatur pemerintah daerah Kota Bukittinggi. (3) menguraikan pengaruh profesionalisme terhadap kinerja aparatur pemerintah daerah Kota Bukittinggi. Objek penelitian ini adalah Organisasi Perangkat Daerah (OPD) di Pemerintah Daerah Kota Bukittinggi. Data yang digunakan adalah data primer dengan menggunakan kuisioner yang di sebar pada 30 OPD dengan populasi 409 orang. Sampel pada penelitian ini adalah aparatur yang terlibat dalam penyusunan anggaran yang terdiri dari Kepala Dinas, Kasubag Perencanaa dan Pejabat Pelaksana Teknis Kegiatan pada Pemerintah Daerah Kota Bukittinggi sebanyak 72 Orang. Dengan menggunakan pendekatan kuantitatif dan analisis data menggunakan model SEM PLS. Hasil penelitian ini menunjukkan bahwa (1) partisipasi penyusunan anggaran berpengaruh posistif dan signifikan terhadap kinerja aparat pemerintah daerah Kota Bukittinggi. (2) kejelasan sasaran anggaran berpengaruh posistif dan signifikan terhadap kinerja aparat pemerintah daerah kota Bukittinggi, (3) Profesionalisme berpengaruh negatif dan tidak signifikan terhadap kinerja aparat pemerintah daerah Kota Bukittinggi.